Penilaian Tingkat Kesehatan Dari Aspek Permodalan Dan Aspek Likuiditas Pada Koperasi Kredit Handayani Kupang - Mikhael Manek (CV. ITTC INDONESIA, 2023)
Based on the description of the background above, the identification of the problem in this study is that the number of current assets, current liabilities and capital owned by the Handayani Kupang Credit Cooperative in 2021 has not provided an overview of the health level of the Handayani Kupang Credit Cooperative from the aspect of liquidity and capital. In addition, based on the results of interviews that the Kupang Handayani Credit Cooperative has not analyzed the level of soundness from the aspect of liquidity and capital. The problem studied in this study can be formulated as follows: How is the health level of the Kupang Handayani Credit Cooperative from the aspect of liquidity and capital?. This research was conducted with the aim of knowing the health level of the Kupang Handayani Credit Cooperative from the aspect of liquidity and capital. This research is classified as descriptive research. Sugiyono (2010) suggests that descriptive research is research conducted on independent variables, namely one or more variables separately without looking for a relationship or influence between one variable and another. The variables in this study are the Cooperative Health Level from the Capital Aspect and the Liquidity Aspect. The data collected was analyzed using the ratio of the assessment of the level of health from the aspect of liquidity and capital according to the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises 06/Per/Dep.6/IV/2016. The steps of data analysis are as follows: (1) Calculating the value of each ratio for the Capital and Liquidity aspects using the formula as stated in the Theory sub-base. (2) Calculating the score of each ratio for the Capital aspect and the Liquidity aspect by means of: the credit value assigned to each ratio value obtained is multiplied by the weight. Credit value and the weight of each ratio for aspects of Capital and aspects of Liquidity as stated in the sub Theory. (3) Interpreting the Health Level of the Kupang Handayani Credit Cooperative in 2019-2021 based on the Capital Aspects and Liquidity Aspects according to the health level category in tables 7, 10 and 11 in the sub-Theoretical Foundation. Based on the results of data analysis, it can be concluded that the total score from the liquidity and capital aspects obtained by the Kupang Handayani Credit Cooperative in 2017-2021 is 17.55%, in 2018 is 19.40%, in 2019, 2020 and 2021 is 17.15 %. The total score obtained in 2017-2021 is in the range of scores for the liquidity and capital aspects of 15.00 < x 22.50 so that the health level of the Kupang Handayani Credit Cooperative is in the Healthy category. The health level which is classified as Healthy category illustrates that: (1) In the aspect of Liquidity, the amount of cash and banks owned by the Handayani Kupang Credit Cooperative is not sufficient to provide guarantees for all of its short-term obligations that must be settled when they fall due. In addition, the Kupang Handayani Credit Cooperative also has not found a balance between the loans given and the funds received where the amount of funds received is greater than the amount of outstanding loans. (2) In the aspect of capital, the Handayani Kupang Credit Cooperative has the ability to obtain the assets needed to run a cooperative business by using its own capital as collateral for risky loans and has the ability to maintain its own capital to control the risks that arise which will affect the sustainability of the cooperative's business. . Based on these conclusions, suggestions can be made for the Management of the Kupang Handayani Credit Cooperative; It is hoped that the management and management: (1) Efforts should be made to have sufficient current assets, especially cash and banks to guarantee all current liabilities that are due and strive that all funds received should be channeled to members in need while taking into account the creditworthiness of each member. . (2) It is necessary to pay attention to adding members in order to increase the amount of own capital as collateral for loans given that are risky so that it does not affect the sustainability of the cooperative's business.